Modeling of filtration and geomigration under anthropogenic impact on groundwater - Medvedieva, O. O.; Dziuba, S. V.; Tiutkin, O. L.; Mashykhina, P. B.; Berlov, O. V. (Science and Transport Progress, 2025)
Purpose. One of the most widespread methods of liquid waste disposal is the use of settling ponds. Wastewater in such lagoons eventually infiltrates into the aeration zone and reaches groundwater. Thus, a chemical contamination area is formed both in the aeration zone and in groundwater. When reengineering sedimentation ponds (for example, when increasing the height of the dam), there is an increase in the pressure in the structure, which will affect the intensity of infiltration of wastewater from the pond into the aeration zone), it is necessary to determine the change in the intensity of environmental pollution in advance. To solve such a forecasting problem, it is necessary to use specialized mathematical models. The aim of the study is to develop numerical models for assessing the dynamics of aeration zone pollution during the infiltration of liquid waste from a sedimentation pond. Methodology. The Laplace equation for the head is used to solve the filtration problem. The process of mass transfer of impurities in the aeration zone is modeled using the mass transfer equation, which takes into account the convective-dispersive transfer of impurities. The numerical integration of the modeling equations is carried out using finite-difference schemes. Findings. Numerical models of filtration and mass transfer are considered, which allow to estimate the dynamics of changes in the contamination area in the aeration zone during the infiltration of liquid wastewater from a sedimentation pond. Originality. The construction of mathematical models for analyzing the infiltration of liquid wastewater from a sedimentation pond is considered. Numerical models take into account the convective-dispersion process of impurity propagation in the aeration area. Practical value. The considered numerical models can be used to assess the environmental impact of sedimentation ponds used for the accumulation of liquid waste.